2014
DOI: 10.4314/sajas.v44i3.4
|View full text |Cite
|
Sign up to set email alerts
|

The effect of <i>Moringa oleifera</i> leaf meal supplementation on tibia strength, morphology and inorganic content of broiler chickens

Abstract: This study was conducted to assess the effects of dietary Moringa oleifera leaf meal (MOLM) supplementation as a possible alternative to antibiotic growth promoters on bone breaking strength (BBS), tibia bone morphology and inorganic ash content in broiler chickens. A total of 2400 one-day-old Cobb-500 broiler chicks of mixed sex were randomly allocated to five dietary treatments in six replications of 80 birds per pen. Dietary treatments were as follows: T1, positive control, 668 g salinomycin and 500 g zinc … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 30 publications
2
13
3
1
Order By: Relevance
“…Similar findings were reported in previous studies (Nkukwana et al, 2016;Qwele et al, 2013). Similar results were reported in the estimation of calcium in tibia bone and ash content with M. oleifera supplementation (Nkukwana et al, 2014b;Gravena et al, 2011). Feed supplemented with MPM significantly affected serum biochemistry (P ≤0.05).…”
Section: Tablesupporting
confidence: 90%
“…Similar findings were reported in previous studies (Nkukwana et al, 2016;Qwele et al, 2013). Similar results were reported in the estimation of calcium in tibia bone and ash content with M. oleifera supplementation (Nkukwana et al, 2014b;Gravena et al, 2011). Feed supplemented with MPM significantly affected serum biochemistry (P ≤0.05).…”
Section: Tablesupporting
confidence: 90%
“…Other authors have similarly reported the antioxidant potential of the leaves of M. Oleifera (Saini et al, 2014b(Saini et al, , 2014d. Other studies showed that M. Oleifera plant may find application in livestock industry for improving meat quality in terms of chemical composition, colour and lipid stability (Nkukwana et al, 2014a(Nkukwana et al, , 2014b(Nkukwana et al, , 2014cQwele et al, 2013). A recent study showed that iron from M. Oleifera can overcome iron deficiency and modulate the expression of iron-responsive genes better than conventional iron supplements (Saini et al, 2014a).…”
Section: Nutritional Value Of M Oleiferamentioning
confidence: 91%
“…Some studies evaluated the addition of simple phytochemicals, such as isoflavone, quercetin, naringin, hesperidin and piperine [32, 9799]. …”
Section: Growth Performancementioning
confidence: 99%